KEPEMIMPINAN SPIRITUAL KIAI DALAM MENINGKATKAN KOMPETENSI MEMBACA DAN MEMAHAMI KITAB KUNING DI PONDOK PESANTREN MAMBAUL ULUM PONDOK WULUH LECES PROBOLINGGO - Amin, Muhammad; Amrullah, AMK.; Kawakip, A. Nurul (re-JIEM (Research Journal of Islamic Education Management), 2022)
This study aims to reveal the form of the kiai’s spiritual leadership values, as well as their relation to the competence to read and understand the yellow book of santri at the Mambaul Ulum Islamic boarding school, Pondok Wuluh Leces Probolinggo. This study uses a qualitative approach. Data was collected through in-depth interviews, observation, and documentation. Data analysis by reducing data, presenting data, and verifying data. Checking the validity of the data using source triangulation techniques and triangulation techniques. Informants in this study were kiai, boarding school administrators, students, and guardians of students. The results showed that: 1) The form of the kiai’s spiritual leadership values â€‹â€‹included true honesty, justice, good deeds, discipline but still flexibility, and humility; 2) The relationship of the kiai’s spiritual leadership with the competence to read and understand the yellow book of santri, namely the kiai as a leader at the Islamic boarding school has full responsibility in all pesantren programs, the kiai as a motivator who inspires students so that students have a disciplined character, are able to awaken the best in themselves, focus on the goal or have a strong desire, seek blessings, and riyaá¸ah.